Nonalcoholic Fatty Liver Disease and Risk of Heart Failure Among Medicare Beneficiaries - Marat Fudim; Lin Zhong; Kershaw V. Patel; Rohan Khera; Manal F. Abdelmalek; Anna Mae Diehl; Robert W. McGarrah; Jeroen Molinger; Cynthia A. Moylan; Vishal N. Rao; Kara Wegermann; Ian J. Neeland; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2021)
Background Nonalcoholic fatty liver disease (NAFLD) and heart failure (HF) are increasing in prevalence. The independent association between NAFLD and downstream risk of HF and HF subtypes (HF with preserved ejection fraction and HF with reduced ejection fraction) is not well established. Methods and Results This was a retrospective, cohort study among Medicare beneficiaries. We selected Medicare beneficiaries without known prior diagnosis of HF. NAFLD was defined using presence of 1 inpatient or 2 outpatient claims using International Classification of Diseases, Ninth Revision, Clinical Modification (ICD‐9‐CM), claims codes. Incident HF was defined using at least 1 inpatient or at least 2 outpatient HF claims during the follow‐up period (October 2015–December 2016). Among 870 535 Medicare patients, 3.2% (N=27 919) had a clinical diagnosis of NAFLD. Patients with NAFLD were more commonly women, were less commonly Black patients, and had a higher burden of comorbidities, such as diabetes, obesity, and kidney disease. Over a mean 14.3 months of follow‐up, patients with (versus without) baseline NAFLD had a significantly higher risk of new‐onset HF in unadjusted (6.4% versus 5.0%; P<0.001) and adjusted (adjusted hazard ratio [HR] [95% CI], 1.23 [1.18–1.29]) analyses. Among HF subtypes, the association of NAFLD with downstream risk of HF was stronger for HF with preserved ejection fraction (adjusted HR [95% CI], 1.24 [1.14–1.34]) compared with HF with reduced ejection fraction (adjusted HR [95% CI], 1.09 [0.98–1.2]). Conclusions Patients with NAFLD are at an increased risk of incident HF, with a higher risk of developing HF with preserved ejection fraction versus HF with reduced ejection fraction. The persistence of an increased risk after adjustment for clinical and demographic factors suggests an epidemiological link between NAFLD and HF beyond the basis of shared risk factors that requires further investigation.